Synthesis and characterization of organic-inorganic lead halide perovskite (CH3NH3PbI3) thin films for photovoltaic applications. (2020) - Benali, H.; Hartiti, B.; Nouri, Y.; Lmai, F.; Batan, A.; Thevenin, P.
Abstract: Solar cells based on hybrid perovskite have marked the world of photovoltaics as a promising photo-absorber material for solar cells, and using inexpensive deposition methods. C H 3 N H 3 P b I 3 have gained significant notice in photovoltaic application as a result of their low fabrication cost and high efficiency that stepped from 3.8% in 2009 to up to 22% in 2018. In the present paper, thin films perovskites were synthesized using low cost method which is the spin coating deposition technique. To obtain the structural characteristic of C H 3 N H 3 P b I 3, X-ray diffraction was employed. The UV–Visible spectroscopy shows the variation of the absorbance in C H 3 N H 3 P b I 3 between wavelengths 300–800 nm.